Pengaruh Citra Perbankan Terhadap Keputusan Nasabah dalam Mengambil Kredit dengan Pelayanan dan Prosedur Kredit Sebagai Variabel Moderating - Putu Krisna Govinda; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine the effect of banking image on customer decisions in taking credit and the influence of banking image on customer decisions in taking credit with credit services and procedures as a moderating variable at PT. BPR Kanaya. This type of research is quantitative research. The population used is all customers who take credit at PT. BPR Kanaya. The sampling technique in this study used the simple random sampling method, with a sample of 139 customers. The data source used is primary data. Data analysis in this research uses descriptive analysis, data quality test, classic assumption test, and hypothesis testing with the help of SPSS program version 23.0. The results showed (1) the banking image had a positive and significant effect on the customer's decision to take credit, (2) the service was able to moderate the influence of the banking image on the customer's decision to take credit, and (3) the credit procedure was able to moderate the influence of the banking image on customer decisions in take kredi